Supply network design and the utilisation of rubber seed oil as biofuel and biochemicals - Ng, Wendy; Lam, H.; Yusup, S. (2012)
This paper presents the supply network design and the utilisation of rubber seed oil (RSO) in Malaysia. Rubber plantation covers about 20% or 1.02 Mha of commercial plantation area in Malaysia (MRB, 2012). At average, 1 ha of land yields 150 kg of oil bearing seeds (Ramadhas et al., 2005). The rubber seeds yields good amount of oil at 30-40 wt% of the seed (Yusup and Khan, 2010). At 20% seeds utilisation, 35 wt% oil extraction ratio and 96 wt% oil conversion rate (Yusup and Khan, 2010a), 10310 t/y of biodiesel could be produced. This increases the country's energy security by developing another potential renewable energy source. RSO has good potential to meet the renewable energy share in Malaysia as well as the growing biodiesel market globally. After extracting oil from rubber seeds, the biomass or seeds left over could be used to feed cows, pigs and other livestock. These applications direct the utilisation of rubber seeds to a zero-waste path. In addition, the supply network of the biomass is synthesised through mathematical programming in this paper. Centralised processing facilities are proposed and optimised biomass distribution network is displayed. A simplified real case study is presented to elucidate the model. Copyright © 2012, AIDIC Servizi S.r.l.